Upaya Meningkatkan Pemahaman Siswa Pada Mata Pelajaran Sejarah Melalui Metode Karya Wisata Di Cagar Budaya Gorontalo Utara: Suatu Penelitian di kelas X SMA Negeri 7 Gorontalo Utara - Sintia Pakaya; Resmiyati Yunus; Andris K. Malae (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to increase students' understanding of history subjects using the field trip method in North Gorontalo cultural heritage in class X SMA Negeri 7 North Gorontalo. By conducting this research, it can be found out that using the field trip method in the North Gorontalo cultural heritage can increase students' understanding of history subjects. The research results found in this study with the use of cultural heritage as a learning medium have not been widely used in history learning. Even though the use of cultural heritage can help students see first-hand the historical heritage in their area. In the research conducted by the researcher, it can be seen that this method was used successfully, students' understanding increased after the field trip method was applied to history learning in the North Gorontalo cultural reserve. This research can see how students respond to learning history. Learning history that is held outside the classroom makes students play an active role and students' curiosity increases compared to learning in the classroom. Keywords: Improving students' understanding, History lessons, Field Trips, North Gorontalo Cultural Heritage, North Gorontalo 7 Public High School